Aplikasi Arsitektur Melayu Kontemporer Studi Kasus : Redesain Pasar Cik Puan Pekanbaru - Indah Lara Syanti; Yohannes Firzal; Mira Dharma Susilawati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
The contemporary approach is one of the solution to preserve the culture while keeping abreast of the times. So it is with Malay Contemporary Architecture through design thatremain based on Malay traditions, but more advanced, varied, flexible and innovative both in form and appearance, material use and technology used to support the latest architecturalstyle. This study aims to identify the application of Malay Contemporary Architecture in new buildings in urban areas. The research methods used include field data collection, literaturestudy and empirical studies. The results of this study confirm that the application principles of Malay Contemporary Architecture can be found among others, through the form of a building that is a transformation of matters related to Malay daily culture, neutral building colors, using renewable materials, creating transparent impressions and varied innovations that different from othersKeywords: Architecture, Malay, Contemporary